A Study On Evaluating Administration Prevalence And Type Of Cancer In Addicted Individuals In Cancer Patients At Multi-Speciality Hospital - Dr.D.Swathi, Dr.Y.Ratna Sindhu , G.Ramya , K.Keerthana , Vinjavarapu L. Anusha ,Dr.D.Curie , Dr.K.Anupama Priyadarshini, Dr.S.R.RAHUL, Dr.G.Kiran (Cuestiones de Fisioterapia, 2025)
Pain is one of the most common symptoms in the cancer population, and cancer-related pain is often treated with opioids. Opioid exposure increases the risk of developing an opioid use disorder (OUD). In addition, a cancer diagnosis can have a significant impact on mental health and wellness, and patients may use substances to cope with psychological distress.